Analysis of Intra-Industry Trade Between Bosnia and Herzegovina and the Western Balkans - Snjezana Brkic (Economic Review: Journal of Economics and Business, 2013)
The paper deals with the issue of intra-industry trade on the example of the trade between Bosnia and Herzegovina and the Western Balkans. The aim of the research is to present the characteristics of Bosnia and Herzegovina trade with the region in the 2004-2011 period, in the context of distinguishing inter- from intra-industry trade. Differentiating between the two types of foreign trade and identifying the structure of intra-industry trade contribute to the identification of a country's trade pattern, and thus to the insight into the level of the country's and its individual industries' competitive ability. The key questions that provided directions for the research include: is the trade between Bosnia and Herzegovina and the region of prevalently inter- or intraindustry character, which type of intra-industry trade prevails in terms of product differentiation (vertical or horizontal), and what is the trend of intra-industry trade intensity in the observed period. The responses deriving from the analysis results reveal the existence of congruence between the pattern of Bosnia and Herzegovina trade with the region and the pattern of the overall Bosnia and Herzegovina trade with the world, which is reflected in the increasing intensity of intraindustry trade, with the still prevailing share of inter-industry trade, dominance of the vertical type of intra-industry trade, and the greatest intensity of intra-industry trade in traditional industries and industries of lower technological level. The results of the research indicate the insufficient convergence of Bosnia and Herzegovina economy with the region's economies, and still unfavorable position compared to partners.
Keywords: F14; 330; intra-industry trade (IIT); Bosnia and Herzegovina (B&H); the Western Balkans (WB)